A self‐help version of the New Forest Parenting Programme for parents of children with attention deficit hyperactivity disorder: a qualitative study of parent views and acceptability. Issue 3 (26th May 2021) - Tarver, Joanne; Daley, David; Sayal, Kapil
Abstract : Background: Although parent interventions are recommended as a frontline treatment approach for children with attention deficit hyperactivity disorder (ADHD), a number of practical and situational barriers can impact accessibility and availability. Self‐help parent interventions offer a potential alternative to therapist‐led interventions when barriers prevent access to face‐to‐face treatment. This qualitative study aims to explore participant views and acceptability of self‐help parent interventions. Method: Semi‐structured interviews were conducted with parents/carers of 12 children (age 6–10 years) with ADHD who received the self‐help version of the New Forest Parenting Programme (NFPP‐SH) as part of a randomised controlled trial. Thematic analysis (as proposed by Braun and Clarke) was used to analyse the data. Results: Overall, participants had favourable views of the self‐help intervention but also experienced some barriers to treatment adherence. Six key themes were identified in parent interviews related to parental desire to learn more; acquisition of new skills; the flexibility of the intervention; self‐help intervention vs. traditional therapist‐led formats; barriers to engagement in the home environment; and need for earlier access to help. Conclusions: NFPP‐SH was an acceptable intervention for parents. However, some parents may need additional support to overcome barriers associated with completing an intervention at home. Implications for healthcare providers and researchers developing self‐help parent interventions for ADHD and child behaviour are discussed.